1999
DOI: 10.1159/000028882
|View full text |Cite
|
Sign up to set email alerts
|

The Endocrine Spectrum of Arachnoid Cysts in Childhood

Abstract: Background: On clinical grounds, arachnoid cysts are usually associated with neurological dysfunction. There is little information concerning their involvement in endocrinological disorders. Patients: The experience in 6 children (birth to 12 years) with hypothalamic-pituitary disturbances secondary to the presence of intracranial arachnoid cysts is reported and the literature is reviewed. Results: Three of our children were diagnosed with isolated hormone abnormalities (2 children with precocious puberty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 19 publications
(18 reference statements)
2
41
0
5
Order By: Relevance
“…In those patients, the possibility that the hGH treatment could have influenced the early onset of puberty is unknown (27). This rare combination of GHD and CPP has been reported essentially in patients with septo-optic dysplasia (6-10) and arachnoid cyst (2)(3)(4)(5). It has also exceptionally been described after a head trauma (7,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those patients, the possibility that the hGH treatment could have influenced the early onset of puberty is unknown (27). This rare combination of GHD and CPP has been reported essentially in patients with septo-optic dysplasia (6-10) and arachnoid cyst (2)(3)(4)(5). It has also exceptionally been described after a head trauma (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…However, GHD has been reported to be associated with CPP in cases of arachnoid cyst (2)(3)(4)(5), septo-optic dysplasia (6-10), brain tumors in the pituitary region, or after cerebral radiation therapy, particularly if administered as prophylaxis against acute lymphoblastic leukemia (11)(12)(13). This association has also been reported in very rare cases after a head injury (7,13).…”
Section: Introductionmentioning
confidence: 98%
“…Precocious puberty, growth hormone deficiency, visual impairment (including blindness), ataxia, head bobbing, and tremor may result when the cyst compresses the adjacent brain. Most suprasellar arachnoid cysts are diagnosed after they have caused symptoms in childhood, 3,4 and very few cases have been diagnosed prenatally before the onset of manifestations. Pierre-Kahn et al 3 reported that out of 20 suprasellar arachnoid cysts studied, 60% were associated with endocrine disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the disorders never regressed postoperatively, even when the decrease of the cyst volume was satisfactory. 3 Mohn et al 4 reported that most pediatric arachnoid cysts have growth hormone deficiency and require hormone replacement therapy even after surgery. In our case, there was a high probability that the child would also have experienced significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…Opponents of conservative therapy point to the risk of hemorrhage and the potential for impaired CNS development. Supporting the case for intervention, Mohn et al [43]reported that children with arachnoid cysts had a greatly increased incidence of endocrine dysfunction. Such dysfunction could be slowly progressive, developing over years [34, 43], and was more frequently associated with suprasellar location [43].…”
Section: Discussionmentioning
confidence: 99%